Mistikisme Kiai dalam Cerpen Kiai Genggong karya Moh. Wan Anwar (Kajian Realisme Magis) - Wijaya, Guntur Sekti; Lestari, Erawati Dwi (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2024)
In Indonesia it is often heard and seen that a situation can occur because there is a mystical element around it. This mystical element goes hand in hand with normal conditions and this has become normal consumption in society. This confusion between reality and mysticism also often appears in the stories of islamic kiai/ulama. They have supernatural powers where these conditions are manifested in the real world so that these real conditions become even more unique with the presence of this mystical element. The supernatural powers within the kiai's body are displayed beautifully in the short story Kiai Genggong by Moh. Wan Anwar. We know that the world of literature does not just create reality as a framework for stories, but mystical elements can also be injected into it. These mystical elements are sometimes inexplicable and supernatural. In it there are strange events so that there seems to be no boundary between the real situation and the supernatural when they collide with each other. By using Wendy B. Faris' theory of magical realism and combining it with Lexy J. Moleong's qualitative research method, this research tries to explore mystical points above the surface of normality in short stories to find out the role and function of mysticism in life. Based on this research, it is known that mysticism in Indonesian islamic boarding schools plays a role as a means of spiritual development and deep understanding of islamic teachings. Its main functions include strengthening the relationship with God, enriching religious experiences, and educating students about moral and ethical values ​​through practices such as dhikr, wirid, and special rituals. Apart from that, mysticism also helps maintain the unique religious traditions and culture in the islamic boarding school environment.